Evaluación de la variación de volumen de granos durante el proceso de hidratación (Vigna Unguiculata) - Chilón Serrano, Leandro (2019)
The objective of this work was to evaluate the variation in the volume of castile bean bean (Vigna Unguiculata) during a hydration process; For this treatment a previous selection of the grain was made, trying to maintain the homogeneous shape of the seed in all the samples. The samples were characterized granulometrically by taking weight and measurements, taking them to Image J software, to determine their shape. The apparent and real density of the samples was obtained, as well as the percentage of initial moisture in the grain for subsequent evaluation. An incubator was conditioned maintaining the constant temperature of the medium at 24 ° C, thus carrying out 21 treatments, of which 20 at periods of time and 1 to 24 hours. The samples were placed in glasses with water (at medium temperature, from their entry), each sample was subsequently withdrawn in its respective time, taking its weight and determining the variation of each treatment by volumetric displacement in a test tube with oil. The results obtained were subjected to 6 mathematical models (Peleg, Kaptso, Page, Weibull, Ibarz-August, Gompertz) analyzed statistically and graphically, thus concluding that Peleg is the optimal model that fits this treatment to assess its behavior.